The Organizational Self-Intiated Expatriate: A Case Study of a Professional Services Firm - Richardson, J.; McKenna, S.; Dickie, Carolyn; de Gama, N. (Palgrave Macmillan, 2013)
Scholarly and practitioner research on the assigned expatriate (AE) is extensive and continues to evolve as global business practices adjust to the changing economic climate. Over the past 15 years or so, and particularly more recently, there has been increasing scholarly interest in what is now widely known as the “self-initiated expatriate” (SIE). The study of expatriates who self-initiate (i.e., rather than being sent by an employer) has emerged in a number of disciplines (Farrer, 2010; Fechter & Walsh, 2010; Korpela, 2010; Leonard, 2010) and reflects the increasing complexity of movement and mobility in the twenty-first century (McKenna & Richardson, 2007). One of the first studies in the field by Inkson, Arthur, Pringle, and Barry (1997) investigated New Zealanders undertaking overseas experience and identified differences from the AE model (Inkson et al., 1997; Inkson & Myers, 2003). Their study makes an important contribution by highlighting a different kind of independent expatriate experience rather than being sent as part of a corporate assignment.